Analisis Kesantunan Berbahasa Mahasiswa dalam Pesan Whatsapp terhadap Dosen Program Studi Pendidikan Bahasa Indonesia : Kajian Pragmatik - Avida Alfi Atuzzahro; Farida Yufarlina Rosita; Berlian Pancarrani (STIKes Ibnu Sina Ajibarang, 2025)
The purpose of this study is to determine the maxims of politeness of language used when communicating with lecturers via WhatsApp. This study uses a qualitative descriptive approach method, data collection techniques, namely interviews and observations, other supporting data, namely screenshots of WhatsApp chats of students and lecturers. And using the word